Draft Strategic Plan 1992-1997 - Trinidad and Tobago. Ministry of Education (Ministry of Education, 1992)
The primary focus of this plan is the Ministry of Education and what it must do: what objectives it should set; what strategies it should adopt; and what programmes, projects and measures it should implement or develop in order to discharge its mission. The discussion is presented under the following topic headings: Basic propositions; 2) Vision statement; 3) Mission and strategic directions; 4) Strengths, weaknesses; opportunities an threats; 5) Strategic objectives and choices; 6) Critical success and factors 7) Implementation; and 8) Summary of programmes.
Keywords: Strategic planning